2019
DOI: 10.15804/tner.19.58.4.04
|View full text |Cite
|
Sign up to set email alerts
|

The Issue of Homeschooling in Poland, the Czech Republic and Slovakia from the Perspective of Parents of Homeschooled Children

Abstract: Th is research addresses the opinions of parents of homeschooled children on the issue of homeschooling. Th rough both quantitative and qualitative research -a questionnaire with 78 parents of homeschooled children from Poland, the Czech Republic and Slovakia, their opinions on the selection of a school for their children, problems in compulsory examination, and the selection of teaching methods and forms were found out. On the basis of the research fi ndings, it was possible to state that criteria for school … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…It can be stated that in Poland, the Czech Republic, and Slovakia the issue of compulsory examination in the umbrella school is not examined in sufficient detail and the ambition of this research is to contribute to solving the issue. The research problem was formulated on the basis of several realized research dealing with the given topic Mazur et al, 2019;Kašparová, 2012;2015;Rochovská et al, 2020;Porubčanová, 2021;Severini et al, 2021).…”
Section: Researched Issuementioning
confidence: 99%
See 1 more Smart Citation
“…It can be stated that in Poland, the Czech Republic, and Slovakia the issue of compulsory examination in the umbrella school is not examined in sufficient detail and the ambition of this research is to contribute to solving the issue. The research problem was formulated on the basis of several realized research dealing with the given topic Mazur et al, 2019;Kašparová, 2012;2015;Rochovská et al, 2020;Porubčanová, 2021;Severini et al, 2021).…”
Section: Researched Issuementioning
confidence: 99%
“…In post-communist countries with a similar educational tradition, such as Poland, the Czech Republic and Slovakia, homeschooling has been studied by reseachers: e.g., Kostelecká (2010), Kašparová (2012;2015), Giercarz-Borkowska, (2019), Hána (2017), Hána and Kostelecká (2019), , , Mazur et al (2019), Rochovská et al (2020), Porubčanová et al (2021), Severini et al (2021).…”
Section: Introductionmentioning
confidence: 99%
“…While in the United States there are about 2.3 million homeschooled pupils, which is about 8% of all pupils (Ray, 2019), in Slovakia, the Czech Republic and Poland, respectively, homeschooling is opted for only by parents of 0.3% of all pupils (Mazur, Rochovská & Kľačková 2019); however, this number is tending to rise. For instance, in the last fi ve years the number of homeschooled children increased from 70 to 579 in Slovakia, from 1038 to 3232 in the Czech Republic and from 2699 to 11466 in Poland (Rochnovská, Mazur & Dolinská, 2019).…”
Section: Viera šIlonovámentioning
confidence: 99%
“…Th e research problem was formulated on the basis of a number of previous studies (Kostelecká, 2010;Kašparová, 2019;Rochovská, Mazur & Dolinská, 2019;Mazur, Rochovská & Kľačková, 2019). As shown in Table 1, it was found that 14.12 % of parents of homeschooled children, participating in the research, preferred unschooling 2 as the main form of education.…”
Section: Research Problemmentioning
confidence: 99%
See 1 more Smart Citation